Encapsulation of Risperidone by Methylated β-Cyclodextrins: Physicochemical and Molecular Modeling Studies - Laura Sbârcea; Ionuț-Mihai Tănase; Adriana Ledeți; Denisa Cîrcioban; Gabriela Vlase; Paul Barvinschi; Marinela Miclău; Renata-Maria Văruţ; Cristina Trandafirescu; Ionuț Ledeți (Molecules, 2020)
Risperidone (RSP) is an atypical antipsychotic drug which acts as a potent antagonist of serotonin-2 (5TH2) and dopamine-2 (D2) receptors in the brain; it is used to treat schizophrenia, behavioral and psychological symptoms of dementia and irritability associated with autism. It is a poorly water soluble benzoxazole derivative with high lipophilicity. Supramolecular adducts between drug substance and two methylated β-cyclodextrins, namely heptakis(2,6-di-O-methyl)-β-cyclodextrin (DM-β-CD) and heptakis(2,3,6-tri-O-methyl)-β-cyclodextrin (TM-β-CD) were obtained in order to enhance RSP solubility and improve its biopharmaceutical profile. The inclusion complexes were evaluated by means of thermoanalytical methods (TG—thermogravimetry/DTG—derivative thermogravimetry/HF—heat flow), powder X-ray diffractometry (PXRD), universal-attenuated total reflectance Fourier transform infrared (UATR-FTIR), UV spectroscopy and saturation solubility studies. Job’s method was employed for the determination of the stoichiometry of the inclusion complexes, which was found to be 2:1 for both guest–host systems. Molecular modeling studies were carried out for an in-depth characterization of the interaction between drug substance and cyclodextrins (CDs). The physicochemical properties of the supramolecular systems differ from those of RSP, demonstrating the inclusion complex formation between drug and CDs. The RSP solubility was enhanced as a result of drug encapsulation in the CDs cavity, the higher increase being obtained with DM-β-CD as host; the guest–host system RSP/DM-β-CD can thus be a starting point for further research in developing new formulations containing RSP, with enhanced bioavailability.